Moplah uprising, 1921-23 - Choudhary, Sukhbir (Agam Prakashan ; Distributed by D.K. Publisher's Distributors, 1977)
On the religion of Moplahs, militant Muslim peasants of the Malabar region, Kerala, against the British.